Homegrown terrorism in the West, 1989 - 2008 - Manni Crone; Martin Harrow (Danish Institute for International Studies (DIIS), 2010)
The London bombings in 2005 led to the perception that the terrorist threat had changed from external to internal. This became conceptualized shortly after as 'homegrown terrorism.' This article deals with the meaning and scope of this phenomenon. We begin by tracing an ambiguity in the term 'homegrown,' which is both about belonging in the West and autonomy from terrorist groups abroad. A quantitative study of Islamist terrorism in the West since 1989 reveals an increase in both internal and autonomous terrorism since 2003 and that most plots are now internal-but not autonomous. Finally, we suggest that an increase in autonomous terrorism is a transitory phenomenon.
Keywords: 330